Pendampingan Ibu-Ibu PKK Kecamatan Lowokwaru Malang melalui Pelatihan Pembuatan Pestisida Nabati sebagai Pengendalian Hama Sayuran Hidroponik - Liliek Harianie; Shinta Shinta; Lila Biarrohmah; Lina Hidayatur Rohmah; Widya Maslahah (Universitas Mathla'ul Anwar Banten, 2020)
GUIDING OF PKK MOTHERS IN LOWOKWARU MALANG DISTRICT THROUGH TRAINING FOR MAKING VEGETABLE PESTICIDES AS A CONTROL OF HYDROPONIC VEGETABLE PEST. In general, chemical pesticides are used to eradicate pests in vegetables. That is because many chemical pesticides are sold in the market and very effective in eradicating pests. The users of chemical pesticides do not understand, if the use of chemical pesticides for a long time and continuously will be very dangerous. Steps that can be taken to prevent the dangers of chemical pesticides is using natural or vegetable pesticides. Vegetable pesticides are more environmentally friendly, the prices are much cheaper, and not dangerous, and the manufacturing process is very easy. The social role of PKK mothers is carried out to improve the activities of coaching, education, training, and counseling. Therefore, it is necessary to conduct socialization and training in the manufacture of plant-based pesticides for PKK mothers in Lowokwaru District, Malang. The methods used include counseling through lectures, direct practice of making vegetable pesticides, and evaluating the process of making vegetable pesticides. The results of a survey of partners showed that 63% of PKK present did not know about vegetable pesticides. In addition, 81% of partners before participating in training activities had never been aware of the process of making vegetable pesticides. Around 90% of partners are known to have never participated in training in making vegetable pesticides. After participating in training and practice in making vegetable pesticides, it is known that 100% of the community service partners have stated that they can increase their knowledge, skills and practice by making vegetable pesticides at home.